Tingkat Pengetahuan Kader Posyandu tentang Pentingnya Pemeriksaan Denver Development Screening Test (DDST) di Posyandu Wilayah Kerja Puskesmas Karya Wanita Rumbai Pekanbaru - Norlita, Wiwik; isnaniar, Isnaniar; Wulandari, Nurfitri (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2021)
In the development of toddlers, cadres have a role in counseling parents (Mothers) regarding child health, monitoring and stimulation/stimulation/early developmental stimuli as well as reporting to health facilities when finding a child who is late in development.. Judging by child health problemsthere is a rate of developmental deviation in children about 10-17 percent. In order to overcome this, early detection is necessary as an effort to plan the implementation program, and determine the prognosis. The purpose of the study was to find out